Defining depth requirements to conserve fish assemblages from water take in an intermittent river - Daniel C. Gwinn; Leah S. Beesley; Bradley J. Pusey; Michael M. Douglas; Chris S. Keogh; Oliver Pratt; Tom Ryan; Mark J. Kennard; Thiaggo C. Tayer; Caroline A. Canham; Lewis G. Coggins; Samantha A. Setterfield (Scientific Reports)
Abstract River systems once safeguarded from water development are being developed. This includes intermittent rivers that annually dry to a series of pools. Describing fish species relationships between abundance and pool depth can help managers set water-take rules that protect fish in dry-season pools. We sampled fish in main-channel and floodplain pools that spanned a gradient of depths and overcame sampling challenges by accounting for interacting effects of species mean length, environmental attributes, and sampling attributes on fish capture probabilities. Fish abundance-depth relationships varied systematically with species mean length, mesohabitat type (main channel, floodplain), water turbidity, and structural complexity, highlighting system complexity and the potential generality of abundance-depth relationships. Similarly, fish length moderated the effects of environmental attributes on capture probability for all sampling methods. We evaluated impacts of hypothetical water-take regulations on fish species’ distributions. Results suggested that water-take rules prohibiting draining of main-channel pools below 1.65 m and reducing floodplain pools by no more than 14% minimises impacts to species’ distributions, promoting conservation of the fish community. Additionally, our approach demonstrates the capacity of species length for predicting distributional and sampling patterns of fish species.